Interplay and clinicopathological correlates of tumor size, multifocality and aggressive variants in patients with operated differentiated thyroid carcinoma: A retrospective cohort study - Gürlüler, Ercüment; Özen, Ali Vuslat (The European Research Journal, 2025)
Objectives: To investigate the interplay and clinicopathological correlates of tumor size, cancer foci (multifocality/bilaterality), and aggressive variants in patients with operated differentiated thyroid cancer (DTC). Methods: A total of 596 patients with operated DTC (median age: 47.0 (range: 18.0-87.0 years, 77.5% were females) were included in this retrospective cohort study. Data on patient demographics, cancer foci, concomitant Hashimoto's thyroiditis, surgery type, DTC subtype (papillary thyroid cancer [PTC], follicular thyroid cancer [FTC]) and variants, tumor size, lymph node metastasis, tumor invasion were recorded. Results: PTC aggressive variant (21.9%, P=0.045), extrathyroidal invasion (24.6%, P=0.012), tall cell PTC variant (60.3%, P=0.043), and widely invasive FTC variants (60.0% P=0.002) rates were significantly higher in the bilateral multifocal tumors than in the unifocal and unilateral multifocal tumors. The rates of Hashimoto's thyroiditis (59.8%, P